Implementation of instruction decoding logic using hardware and software [electrinic resource] - Su, Chee Siong, 1982- (2010)
Thesis (Sarjana Kejuruteraan (Elektrik - Komputer dan Mikroelektronik)) - Universiti Teknologi Malaysia, 2010